DAMPAK EKONOMI PERKEBUNAN BESAR KELAPA SAWIT TERHADAP KEHIDUPAN MASYARAKAT DI NAGARI SALAREH AIA BARAT KECAMATAN PALEMBAYAN AGAM (Studi Kasus PT. AMP Plantation) - Ade Sri Novianti; Rusda Khairati; Rini Hakimi (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
In Indonesia, the development of oil palm plantations in 2018-2022 continues to increase every year, consisting of State-Owned Enterprises (PBN), Private Companies and People's Plantations, the largest oil palm plantations are private companies because the producers of the best plantation product commodities, one of which is produced by Indonesia, can help improve the economy and employment. This is what makes domestic and foreign investors interested in investing in the form of oil palm plantations as producers of export CPO. This study aims to analyze the economic impact of large oil palm plantations on people's lives and factors influencing economic development. The method uses a qualitative method. The population uses 3 key informants and 30 samples with a purposive sampling technique. The results of the study found that the economic impact of large oil palm plantations on people's lives is in the form of: increased income as seen from the increase in the amount of income received by the community. The reduction in unemployment is seen from the majority of people who currently work in companies and work in other fields such as trading and becoming palm oil collectors, the increase in business opportunities for the community is seen from the increasing number of businesses developed by the community such as selling daily necessities, renting shophouses, and becoming household assistants. Factors that influence the economic development of the community are the natural resources owned by the community, the land is fertile, human resources have sufficient knowledge about oil palm cultivation, the technology used by modern and traditional communities, the smart work culture that has been cultivated by the community and the capital resources owned by the community.